Humanitarian Diplomacy of European Union in the 21st Century - O. N. Bogatyreva (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to the areas of diplomacy of the European Union, which are closely related to the human factor and the principles of human rights, tolerance and culture of peace. Particular attention is paid to theoretical and methodological problems of a new model of diplomacy, to the analysis of the concept of “humanitarian diplomacy” combined with the concept of “soft power.” The question is raised that modern humanitarian diplomacy is not limited to the provision of humanitarian assistance, but includes the protection of rights and freedoms, assistance to vulnerable persons, educational and cultural cooperation, social programs, and peacekeeping. The main directions, principles and tools of the EU humanitarian diplomacy are considered. It is shown that humanitarian aid and civil protection in different regions of the world is a priority direction. Other areas of humanitarian diplomacy, including the protection of human rights, cultural relations and intercivilizational dialogue, “vaccine diplomacy,” are also under consideration. It is noted that activities of the EU in all areas of its foreign policy without exception is based on the promotion of human rights. The authors conclude that in the 21st century the EU humanitarian diplomacy is an effective tool of global dialogue, necessary for sustainable development and peaceful resolution of conflicts.